Aerodynamic performance evaluation of sports textile - Chowdhury, H.; Alam, F.; Subic, A. (Procedia Engineering, 2010)
Aerodynamics play a significant role in high performance textiles across a wide range of sports including cycling, skiing, bobsleigh, sprint, and speed skating. Considerations in this aerodynamic performance include the textile surface morphology, fastener placement and air permeability. Elite competition usually involves very short winning time margins in events that often have much longer timescales, making aerodynamic resistance and its associated energy loss during the event significant in the outcome. This paper describes the impact of textile surface employing a standard cylindrical arrangement in wind tunnel studies to provide data on aerodynamic drag and lift as a function of athlete's body positions together with textile surface morphology.